1998
DOI: 10.1016/s0022-5223(98)70455-6
|View full text |Cite
|
Sign up to set email alerts
|

Biologic bypass with the use of adenovirus-mediated gene transfer of the complementary deoxyribonucleic acid for vascular endothelial growth factor 121 improves myocardial perfusion and function in the ischemic porcine heart

Abstract: An Ad vector expressing the VEGF121 cDNA induces collateral vessel development in ischemic myocardium and results in significant improvement in both myocardial perfusion and function. Such a strategy may be useful in patients with ischemic heart disease in whom complete revascularization is not possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
156
0
3

Year Published

1999
1999
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 286 publications
(160 citation statements)
references
References 26 publications
1
156
0
3
Order By: Relevance
“…16 Recently, the recombinant Ad expressing VEGF 121 was shown to protect against ischemic vascular occlusion in a rat limb and to improve myocardial perfusion in the porcine ischemic heart. 14,15 In the study at hand, the human bFGF gene was expressed under the control of the RSV promoter. We have shown that expression of RSV promoter-driven genes can last several weeks in immunocompetent hosts and several months in nude mice after intramuscular injections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Recently, the recombinant Ad expressing VEGF 121 was shown to protect against ischemic vascular occlusion in a rat limb and to improve myocardial perfusion in the porcine ischemic heart. 14,15 In the study at hand, the human bFGF gene was expressed under the control of the RSV promoter. We have shown that expression of RSV promoter-driven genes can last several weeks in immunocompetent hosts and several months in nude mice after intramuscular injections.…”
Section: Discussionmentioning
confidence: 99%
“…Replication-deficient adenoviruses have been recently used to transfer various genes coding other potent angiogenic factors. [10][11][12][13][14][15] Ad vectors present several advantages including: (1) a low pathogenicity in nonimmunosuppressed individuals; (2) a high capacity to accept foreign DNA; (3) high viral titers; (4) an efficient gene expression in quiescent cells such as skeletal muscle fibers or cardiomyocytes and (5) a transient expression in dividing cells, which is particularly adapted to the time course of vessel neoformation. 16 In counterpart, adenovirus vectors induce inflammatory and immune responses and the current vectors employed are not tissue specific.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Preclinical studies have demonstrated that delivery of the VEGF gene into ischemic tissue can stimulate the development of collateral arteries in animal models of peripheral and myocardial ischemia. [39][40][41][42] Adenovirus-mediated gene delivery has the ability to deliver high concentrations of proteins such as VEGF to a localized area within ischemic tissue, while minimizing the risks associated with systemic administration of angiogenic factors. Studies by our group have confirmed that high levels of localized VEGF are generated within skeletal muscle upon intramuscular injection of Ad-VEGF 121.…”
Section: Introductionmentioning
confidence: 99%
“…9 Thus, the significance of improvements in collateralization after administration of VEGF protein or VEGF gene therapy suggested by other studies is unclear. 5,6,10,11 Effects of pVEGF 165 gene transfer on regional myocardial blood flow: spatial 'delivery-efficacy' mismatch…”
Section: Angiographic Assessment After Pvegf 165 Transfermentioning
confidence: 99%
“…Previous preclinical studies using microsphere techniques may have underestimated the angiogenic efficacy when tissue samples were selectively taken from the treated myocardial segments. 5,6 Sensitive noninvasive imaging techniques providing regional assessment of blood flow such as positron emission tomography and MRI may overcome this problem in preclinical studies, and are already being evaluated in clinical angiogenesis trials. [14][15][16] In conclusion, plasmid VEGF 165 delivery by direct intramyocardial injection to the pig myocardium improves regional perfusion but only in areas adjacent to the site of administration into a region of ischaemia.…”
Section: Angiographic Assessment After Pvegf 165 Transfermentioning
confidence: 99%